Analiza przyczyn biegunki ostrej u niemowląt jako wyznacznik profilaktyki pierwotnej i wtórnej = Analysis of the causes of acute diarrhea in infants as a marker of primary and secondary prevention - Stadnicka, Sabina Katarzyna; Brodowicz-Król, Magdalena; Trojanowska, Alina; Zarzycka, Danuta (Journal of Education, Health and Sport, 2016)
Stadnicka Sabina Katarzyna, Brodowicz-Król Magdalena, Trojanowska Alina, Zarzycka Danuta. Analiza przyczyn biegunki ostrej u niemowląt jako wyznacznik profilaktyki pierwotnej i wtórnej = Analysis of the causes of acute diarrhea in infants as a marker of primary and secondary prevention. Journal of Education, Health and Sport. 2016;6(7):91-102. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57157 http://ojs.ukw.edu.pl/index.php/johs/article/view/3670 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016. Analiza przyczyn biegunki ostrej u niemowląt jako wyznacznik profilaktyki pierwotnej i wtórnej Analysis of the causes of acute diarrhea in infants as a marker of primary and secondary prevention Sabina Katarzyna Stadnicka, Magdalena Brodowicz-Król, Alina Trojanowska, Danuta Zarzycka Katedra i Zakład Pielęgniarstwa Pediatrycznego, Wydział Nauk o Zdrowiu, Uniwersytetu Medycznego w Lublinie Sabina Katarzyna Stadnicka, mgr położnictwa, doktorantka, Katedra i Zakład Pielęgniarstwa Pediatrycznego, Wydział Nauk o Zdrowiu, Uniwersytetu Medycznego w Lublinie; Magdalena Brodowicz-Król, mgr pielęgniarstwa, mgr pedagogiki, asystent Katedra i Zakład Pielęgniarstwa Pediatrycznego, Wydział Nauk o Zdrowiu, Uniwersytetu Medycznego w Lublinie Alina Trojanowska, dr n. med., adiunkt, Katedra i Zakład Pielęgniarstwa Pediatrycznego, Wydział Nauk o Zdrowiu, Uniwersytetu Medycznego w Lublinie Danuta Zarzycka, dr hab. n. o zdrowiu, adiunkt, Katedra i Zakład Pielęgniarstwa Pediatrycznego Wydział Nauk o Zdrowiu, Uniwersytetu Medycznego w Lublinie Streszczenie Wprowadzenie: W populacji dziecięcej jednym z najczęstszych zaburzeń rytmu wypróżniania są biegunki. Na ostrą biegunkę choruje praktycznie każde dziecko poniżej 3. roku życia. Cel: Celem pracy jest przedstawienie przyczyn występowania i zasad postępowania w biegunce ostrej u niemowląt ze zwróceniem szczególnej uwagi na profilaktykę i postępowanie przedszpitalne. Metoda: Przegląd tematyczny literatury przedmiotu obejmujący okres od 2006 do 2016 roku. Wyniki: Za większość ostrych nieżytów żołądkowo-jelitowych odpowiedzialne są zakażenia rota wirusowe. Infekcje mogą mieć zróżnicowany przebieg. Zakażenie o łagodnym przebiegu, charakteryzuje się wodnistymi stolcami, współwystępowaniem wymiotów oraz nieżytu górnych dróg oddechowych. Przebieg ciężki biegunki często powoduje powstanie objawów znacznego odwodnienia i zaburzenia gospodarki wodno-elektrolitowej i kwasowo-zasadowej. Pojawiająca się krew w stolcu świadczy o współistniejącym zakażeniu bakteryjnym. Podstawowym postępowaniem w trakcie biegunek jest wypełnienie łożyska naczyniowego za pomocą doustnych płynów nawadniających. W niektórych przypadkach konieczne jest leczenie w warunkach szpitalnych. Podsumowanie: Ze względu na najczęstszą etiologię biegunki u dzieci, czyli zakażenia wirusowe i łatwość przenoszenia zakażeń, profilaktykę opiera się na zachowaniu szczególnej dbałości o higienę (w tym przede wszystkim częste mycie rąk). Słowa kluczowe: biegunka ostra, niemowlęta, rotawirusy, profilaktyka. Abstract Introduction: in the pediatric population one of the most common irregular bowel movements are diarrhea. Acute diarrhoea have virtually every child below 3. year of life. Objective: the aim of the work is the presentation of the causes of and the rules of conduct in acute diarrhea in infants with special attention to the prevention and treatment przedszpitalne. Method: a review of thematic literature covering the period from 2006 to 2016. Results: the most acute gastrointestinal infection are responsible nieżytów rota virus. Infections can be differentiated. Mild infection, characterized by wodnistymi stools, interaction of vomiting and respiratory tract mucus secretion. The course of severe diarrhea often causes signs of significant dehydration and disorders of water and electrolyte and acid-base. That appears to be blood in the stool indicates a particular bacterial infection. The primary consideration in the course of diarrhea is to fill the vascular bed using oral irrigation fluids. In some cases it is necessary to treatment in a hospital. Summary: due to the most common etiology of diarrhea in children, that is, viral infections and ease of cross infection, prevention is based on maintaining special attention to hygiene (including especially frequent hand washing). Key words: acute diarrhea, infants, Rotarix, prevention.